Influence Of English on Uzbek Aviation Terms (Texas Journal of Philology, Culture and History, 2022)
The article discusses the features of aviation terminology in English, and also describes the difficulties that a translator faces when translating technical literature. The analysis of terms is based on examples from the Dictionary of International Civil Aviation.